Край еловый, сосновый, берёзовый...: избранное / Тамара Кудрявцева - Кудрявцева Тамара Васильевна (2004)
Экземпляры: УКП (20210220) / Инвентарный номер: АП20040813 / Сис.шифр: 84(2) / Авт.знак: К 88 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4